2018
DOI: 10.1111/tbed.13076
|View full text |Cite
|
Sign up to set email alerts
|

Generation of monoclonal antibodies against foot‐and‐mouth disease virus SAT 2 and the development of a lateral flow strip test for virus detection

Abstract: Foot‐and‐mouth disease (FMD) remains a major economic concern for the livestock productivity in many developing countries and a continued threat to countries that are disease free because of its potential devastating impact on agricultural, food chain and tourism sectors. FMD virus (FMDV) is recognized as having seven serotypes: O, A, C, Asia 1, South African Territories (SAT) 1, 2, 3 and multiple subtypes within each serotype. FMD outbreaks due to SAT 2 have been reported in many African countries. The develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…However, antigen detection by LFI was short-lived compared to rRT-PCR, implying that LFI might fail to detect low levels of viral antigen in MJ. rRT-PCR is inherently a more sensitive assay [ 20 ] and thus explains the detection of FMDV RNA over a wider duration of the experiment. The fact that LFI can detect FMDV in MJ is a good reason to collect both MJ and sera when possible, considering that FMDV antigen detection in serum samples by LFIs has not been successful [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, antigen detection by LFI was short-lived compared to rRT-PCR, implying that LFI might fail to detect low levels of viral antigen in MJ. rRT-PCR is inherently a more sensitive assay [ 20 ] and thus explains the detection of FMDV RNA over a wider duration of the experiment. The fact that LFI can detect FMDV in MJ is a good reason to collect both MJ and sera when possible, considering that FMDV antigen detection in serum samples by LFIs has not been successful [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meat juice samples from naïve and FMDV–infected pigs were tested for antigen by LFI for FMDV serotype A [ 21 ] and FMDV serotype SAT 2 [ 20 ] following the published protocols for each serotype. Each test utilizes two conjugated serotype-specific monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse sets of MAbs against FMDV have been generated by murine hybridoma technology [ 7 , 8 , 9 , 10 ]. Extensive studies on antigenic features of FMDV, especially type O, have identified major neutralizing epitopes recognized by the mouse MAbs [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antigen detection and molecular assays have been evaluated for this purpose. Lateral flow strip tests (LFSTs) for FMDV antigen detection are available, some of which are being used in the field (Ferris et al, , ; Yang, Caterer, Xu, & Goolia, ; Yang, Goolia, Xu, Bittner, & Clavijo, ; Yang, Mudabuka, Quizon, & Nfon, ). LFST was used for FMD detection during the 2007 FMD outbreak in the UK (Ryan et al, ).…”
Section: Introductionmentioning
confidence: 99%